Acceleration of TDP43 and FUS/TLS protein expressions in the preconditioned hippocampus following repeated transient ischemia. Issue 1 (28th October 2013) - Sun, Miao; Yamashita, Toru; Shang, Jingwei; Liu, Ning; Deguchi, Kentaro; Liu, Wentao; Ikeda, Yoshio; Feng, Juan; Abe, Koji
<x xml:space="preserve">Abstract</x> The 43‐kDa transactivation response DNA binding protein (TDP43), fused in sarcoma/translocated in liposarcoma (FUS/TLS), heat shock protein 70 (HSP70), and β‐amyloid (Aβ) are induced and involved in cerebral ischemia, amyotrophic lateral sclerosis (ALS), and Alzheimer's disease (AD), but their relationships in ischemic tolerance have never been examined, although they could be involved in endogenous neuroprotection under ischemic preconditioning. In the present study, Mongolian gerbils were subjected to one or three incidents of basically nonlethal 2‐min transient common carotid arteries occlusion (tCCAO). Hippocampal CA1 neurons were lost only in the 2‐min three times group at 3 and 7 days, which then gradually recovered from 1 to 6 months. Inductions of TDP43 and FUS/TLS were accelerated from 3 months to 7 days or from 7 days to 1 day, respectively, after 2‐min three times ischemia compared with once. The cytoplasmic stainings of TDP43 and FUS/TLS showed a further acceleration of the peaks from 1 months to 3 days or from 1 months to 7 days, respectively, after 2‐min three times ischemia compared with once. In contrast, HSP70 was induced only at 7 days after 2‐min tCCAO for three times, with no expression for Aβ. These data show that ischemic preconditioning offers a way to induce endogenous neuroprotection and neurogenesis in gerbils, with TDP43, FUS/TLS, and HSP70 involved in this function. © 2013 Wiley Periodicals, Inc.